How do women's self-report symptoms impact on identification of perinatal mental health problems?. Issue 3 (8th May 2017) - Jarrett, Patricia M.
Abstract : Purpose: Perinatal depression is common and increases the risk of adverse outcomes for both the mother and child. Despite regular contact with midwives and GPs during the perinatal period less than 50 per cent of women with depression are identified and treated. A number of reasons for this have been proposed; however, failure of health professionals to recognise the symptoms women present with may contribute. The purpose of this paper is twofold: to explore women's self-report symptoms of perinatal depression and understand how the symptoms women present with might impact on identification. Design/methodology/approach: Women were invited to post their experiences of perinatal depression on one of two online discussion forums over a nine-month period. Data were analysed using a process of deductive thematic analysis informed by cognitive behavioural therapy. Findings: Women's symptoms were presented using five headings: triggers (for perinatal depression), thoughts, moods, physical reactions and behaviours. Women believed having a previous mental health problem contributed to their depression. Women's self-report symptoms included intrusive and violent thoughts; emotional responses including fear, worry and anger; and somatic symptoms including insomnia and weight changes. Women also reported aggressive behaviour and social withdrawal as part of their depressive symptomatology. Symptoms women present with may negatively impact on identification as they often overlap with those of pregnancy; may not be included in the criteria for mental health assessment and may involve undesirable and socially unacceptable behaviour, making disclosure difficult. Practical implications: A more inclusive understanding of women's self-report symptoms of perinatal depression is called for, if identification is to improve. Originality/value: This paper offers an analysis of women's self-report symptoms of depression, in the context of identification of perinatal mental health problems.